WOMEN’S INEQUALITY AS INFLUENCE OF SOCIAL DISCRIMINATION IN MEMOIRS OF GEISHA BY ARTHUR GOLDEN - Vidie Alfadina Effendy; Adi Prautomo (Prologue: Journal on Language and Literature, 2024)
This research explored the features of women's inequality as the influence of social discrimination in the novel Memoirs of a Geisha by Arthur Golden. There are two objectives in this research; 1) To find out the forms of women’s inequality in the novel Memoirs of Geisha by Arthur Golden. 2) To examine how women's inequality is influenced by social discrimination in Arthur Golden's novel Memoirs of Geisha. The theory used in this research is Rosemarie Tong’s Marxist Feminism, and the research methodology used is qualitative research in which the researcher presents the issues descriptively. As for the data, they were collected from the narration and dialogue in the novel. The result of the research, the researcher found the forms of women's inequality which are Sexual Harassment, Slavery, Subordination, and Violence, and for the second research, the researcher found the influence of social discrimination which are Dialectical materialism, Historical materialism, Class Struggle, Alienation, and Revolution.